Philosophical reasons for choosing the IB Programme for the internationalization strategy at the Al Firdaus Educational Institution Foundation - Yahya, Nadjibah; Giyoto, Giyoto; Maslamah, Maslamah; Ma’ruf, Imam (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study aims to find out the philosophical reasons for choosing the International Baccalaureat (IB) programme as an internationalization strategy at Yayasan Lembaga Pendidikan Al Firdaus (YLPAF) and find out the preparation using the IB curriculum. This research is qualitative research with action research methods. Data collection techniques with observations, interviews, and documents. Those studied were YLPAF directors, principals and teachers. Data analysis used interactive analysis. Data validity methods used with triangulation of data sources. The results of this study are the philosophical reasons why YLPAF chose the IB curriculum because the IB program teaches character and IB does not change the initial concept of Al Firdaus as an inclusive and Islamic school. The preparations made by YLPAF in preparing for IB authorization are as follows: improving human resource skills at YLPAF, especially in the fields of IT and English, train all stokeholders towards the IB programme, carry out all activities recommended in the IB programme so that the concept of IB is more quickly recognized and absorbed by YLPAF.